2006
DOI: 10.4049/jimmunol.176.2.1203
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Adjuvant Monophosphoryl Lipid A Triggers Various Immune Responses, but Not Secretion of IL-1β or Activation of Caspase-1

Abstract: Lipid A, the membrane anchor portion of LPS, is responsible for the endotoxin activity of LPS and induces many inflammatory responses in macrophages. Monophosphoryl lipid A (MPL), a lipid A derivative lacking a phosphate residue, induces potent immune responses with low toxicity. To elucidate the mechanism underlying the low toxicity of MPL, we examined the effects of MPL on the secretion of proinflammatory cytokines by mouse peritoneal macrophages, a murine macrophage-like cell line (RAW 264.7), and a human m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 37 publications
10
66
0
Order By: Relevance
“…Secretion of IL-1P induced by TLR4 agonists in the absence of exogenous ATP is codependent on MyD88 and TRIF Previous studies have reported weak IL-1f3 production by MLA [17,47]. We confirmed this finding in myeloid DCs using synthetic MLA to stimulate the cells in the absence of exogenous ATP, which showed weak production of IL-1f3 at all doses when compared to Lipid A.…”
Section: Statistical Analysis and Sample Normalizationsupporting
confidence: 85%
See 3 more Smart Citations
“…Secretion of IL-1P induced by TLR4 agonists in the absence of exogenous ATP is codependent on MyD88 and TRIF Previous studies have reported weak IL-1f3 production by MLA [17,47]. We confirmed this finding in myeloid DCs using synthetic MLA to stimulate the cells in the absence of exogenous ATP, which showed weak production of IL-1f3 at all doses when compared to Lipid A.…”
Section: Statistical Analysis and Sample Normalizationsupporting
confidence: 85%
“…TLR4 signaling alone is sufficient for production of significant levels of the inflammatory cytokine IL-1J3 [47], and although the levels of IL-1J3 produced by this mechanism are lower than with activation by experimental addition of A TP, they may be relevant in situations of chronic inflammation. For example, DAMPs recognized by TLR4 have been implicated in the pathogenesis of several inflammatory conditions including diabetes, arthritis, systemic lupus erythematosus, septic shock, stroke and myocardial infarct as well as Alzheimer and Crohn's disease, each of which has been linked to aberrant production of IL-1J3 and/or NLRP3 activation [67][68][69][70][71][72][73].…”
Section: Statistical Analysis and Sample Normalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, adjuvants can have pleomorphic effects on a variety of cell types and this is much less appreciated. For example, monophosphoryl lipid As (MPLs) and its more toxic parent compound, LPS are thought to interact mainly via TLR4 ligation, but these compounds have differing effects on T cells and cytokine production [2][3][4][5][6][7][8][9][10]. The different cell types stimulated by MPL and LPS further add to the complexity of the effects of the adjuvants [2][3][4]9,11].…”
Section: Introductionmentioning
confidence: 99%